A Comparison of the Injection Rate of Local Anesthetic during Spinal Anesthesia on the Onset of Sensory Block and Incidence of Hypotension in Caesarean Section - Ersagun Tugcugil; Ahmet Besir (Clinical and Experimental Obstetrics & Gynecology)
Objective: The injection rate of the local anesthetic may affect the level and the time of onset of sensory block. The aim of this prospective study was to investigate the effects of two different injection rates of local anesthetic solution (0.5% heavy bupivacaine) on the onset of sensory block, and the incidence and the onset of hypotension in pregnant women undergoing spinal anesthesia for elective Cesarean delivery. Methods: A total of 67 patients were randomized into two groups: 120-second injection time (Group Slow; n = 33) and 15-second injection time (Group Fast; n = 34). Maximum level of sensory and motor block, time to sensory block at the level of T6, hemodynamic parameters, use of ephedrine and incidence of side effects were recorded at measurement time points. Results: Maximum level of the sensory block was similar in both groups. The time to achieve adequate and maximum sensory block level was shorter in Group Slow(S) (p = 0.004 and 0.037, respectively). Incidence of hypotension was similar, but hypotension occurred earlier in Group Fast(F) (p = 0.011). Requirement for ephedrine and incidence of nausea and vomiting was similar. Conclusions: This study reveals that 120-second injection duration during spinal anesthesia is associated with shorter time to achieve the maximum sensory block level and slower onset of hypotension. It means that prolonging the duration of local anesthetic injection to 120-seconds is advantageous compared with 15-seconds in caesarean section.